Factors related to orientation of search for dental care in high risk pregnancy - Jessica Galvan; Danielle Bordin; Cristina Berger Fadel; Fabiana Bucholdz Teixeira Alves (Instituto Materno Infantil de Pernambuco, 2022)
Abstract Objectives: to relate the search for dental care during pregnancy to sociodemographic, gestational and dental characteristics. Methods: quantitative approach study with cross-sectional design carried out with high-risk pregnant women, from January to May 2018. Statistical analysis was performed using Pearson's chi-square association test and Fisher's exact test, followed by logistic regression analysis and odds ratio calculation. Results: the final sample was composed of 190 pregnant women and the guidance for seeking dental care was significantly related to issues related to Prenatal Dental Care, regarding safety (p = 0.025), effective search (p < 0.0001) and the Unit Basic Health Care as a place of assistance (p = 0.0018). Pregnant women who did not receive search guidance are 19.6 more likely to not seek this service (p <0.001), when they seek it without guidance, they have 6.3 more chances to seek private services (p = 0.014) and when they do not receive guidance, they are 4.5 more likely to not feel secure in relation to this assistance (p = 0.005). Conclusion: the guidance and encouragement provided by the health team is paramount in pregnant woman's decision to seek assistance, especially in the context of Primary Health Care, and is characterized as a strategic tool in reducing insecurities related to dental treatment during pregnancy.